Pengaruh ChatGPT Terhadap Proses Pembelajaran Mahasiswa di Institut Teknologi Sepuluh Nopember - Nur Nindya Risnina; Septica Tiara Indah Permatasari; Aliyya Zahra Nurulhusna; Febina Mushen Anjelita; Cahya Wulaningtyas; Nur Aini Rakhmawati (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
With the advancement of technology, more and more OpenAI products have emerged, one of which is ChatGPT. The use of ChatGPT has been widely adopted, particularly in the field of education. Numerous previous studies have shown that the use of ChatGPT in the learning process has a positive impact. Therefore, this research aims to determine students' preferences for the use of ChatGPT in the learning process. This study employed a descriptive method with a quantitative approach and will be measured using a Likert Scale. The research showed that most students gave a positive response to the use of high-scale ChatGPT to assist the learning process in lectures because of the role and benefits provided by ChatGPT in three aspects of the learning process, including student engagement, material understanding, and learning effectiveness.